2021
DOI: 10.14740/cr1254
|View full text |Cite
|
Sign up to set email alerts
|

Small Dense Low-Density Lipoprotein for Risk Prediction of Acute Coronary Syndrome

Abstract: Background: Elevated Low density Lipoprotein (LDL) levels have been traditionally associated with development of atherosclerotic coronary artery disease (CAD). As LDL-cholesterol levels are not always raised in acute coronary syndrome (ACS) patients, sd-LDL is an emerging risk factor. The purpose of the present study was tri-fold. Firstly, it aimed to investigate the association of sd-LDL as a risk factor in ACS patients. Secondly, it aimed to correlate the presence of sd-LDL with severity of coronary artery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…AIP is directly proportional to the increased number of sdLDL particles and inversely proportional to LDL-C particle size [29,30]. In a previous study, the relationship between sdLDL and CAD has been demonstrated, and it has been shown that sdLDL plays a role in the atherosclerotic process [31]. Accordingly, increased AIP values in patients with obstructive CAE may be an indirect indicator of sdLDL values.…”
Section: Discussionmentioning
confidence: 94%
“…AIP is directly proportional to the increased number of sdLDL particles and inversely proportional to LDL-C particle size [29,30]. In a previous study, the relationship between sdLDL and CAD has been demonstrated, and it has been shown that sdLDL plays a role in the atherosclerotic process [31]. Accordingly, increased AIP values in patients with obstructive CAE may be an indirect indicator of sdLDL values.…”
Section: Discussionmentioning
confidence: 94%